Hubungan Keterampilan Dasar Konseling dengan Minat Siswa Mengikuti Konseling Individu - Mahadhita, Fitriana; Kurniawan, Kusnarto (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
Interest is an important factor of students participating in individual counseling service. Student’s interest inparticipating in individual counseling service can be influenced by counseling basic skill are mastered counselor. The purpose of this research is to describes the relation between the counseling basic skills with the students participation interest in individual counseling service at SMA Negeri 1 Godong.The method used in this research is a quantitative correlation method. The population in this research were all students of SMA Negeri 1 Godong who attended individual counseling services, with total of 55 students. The sampling technique used is saturated Sampling. Method of data collection used is the scale of interest and scale student’s perception of counseling basic skill are mastered counselor. Data analysis used is percentage descriptive analysis and simple linear regression analysis. The results showed that the counseling basic skills classified in the high category (75.49%) and the students interest of participating individual counseling service was high (79.31%). As well as there is a significant relationship between the counseling basic skills with the students interest of participating the individual counseling service.